2001
DOI: 10.1007/bf02668091
|View full text |Cite
|
Sign up to set email alerts
|

Specific targeting of folate–dendrimer MRI contrast agents to the high affinity folate receptor expressed in ovarian tumor xenografts

Abstract: The need to develop target-specific MRI contrast agents to aid in disease characterization remains highly essential. In this study, we present a generation four polyamidoamine (PAMAM) folate-dendrimer that specifically targets the high affinity folate receptor (hFR) overexpressed on more than 80% of ovarian tumors. In vitro, mouse erythroleukemia cells expressing the hFR bind the radiolabeled folate-dendrimer chelate resulting in over 2700% increase in binding compared with untreated cells. The binding was inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
81
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(81 citation statements)
references
References 36 publications
0
81
0
Order By: Relevance
“…In tumor imaging, antibody-SPIO conjugates were able to be used to successfully image numerous surface markers overexpressed in tumor vessels and cells, such transferrin receptor [115], folic acid receptor [116], VEGF [117], RGD [118], α ν β 3 -integrin as angiogenesis marker [119], Her2/neu (cerb B-2) tyrosinase receptor [114], uMUC-1 [120], LHRH-R [121], EGFR [122], CEA [123], CEACAM5 ( • " Fig. 5) [124], CXCR4 [125], CD20 [126] or B220 + (B-cell lymphomas) [127] with the help of T2w or T2*w MRI.…”
Section: Tumor Imagingmentioning
confidence: 99%
“…In tumor imaging, antibody-SPIO conjugates were able to be used to successfully image numerous surface markers overexpressed in tumor vessels and cells, such transferrin receptor [115], folic acid receptor [116], VEGF [117], RGD [118], α ν β 3 -integrin as angiogenesis marker [119], Her2/neu (cerb B-2) tyrosinase receptor [114], uMUC-1 [120], LHRH-R [121], EGFR [122], CEA [123], CEACAM5 ( • " Fig. 5) [124], CXCR4 [125], CD20 [126] or B220 + (B-cell lymphomas) [127] with the help of T2w or T2*w MRI.…”
Section: Tumor Imagingmentioning
confidence: 99%
“…gadomers) have been further explored alone, 8-10 conjugated to avidin/biotin, 11 conjugated to monoclonal antibodies, 12 or targeted to high-affinity folate receptors. 13 Shukla and co-workers evaluated a non-MRI-based, fluorescently labeled generation 5 PAMAM dendrimer modified with doubly-cyclized RGD peptides containing two disulfide linkages via four cysteine residues. 14 Langereis and co-workers reported the synthesis of a Gd(III)-DTPA-functionalized dendritic contrast agent modified with a cyclic NGR sequence to encourage preferential binding to tumor vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…25 So far, some papers regarding folate-appended dendrimers have been published. For example, Konda et al 26 reported the novel folate dendrimer magnetic resonance imaging contrast agents to the high affinity FR expressed in ovarian tumor xenografts. Shukla et al 27 demonstrated the FR-targeted boronated dendrimers as potential agents for neutron capture therapy.…”
Section: Introductionmentioning
confidence: 99%